2015
DOI: 10.1021/nl5040946
|View full text |Cite
|
Sign up to set email alerts
|

Sb-Induced Phase Control of InAsSb Nanowires Grown by Molecular Beam Epitaxy

Abstract: For the first time, we report a complete control of crystal structure in InAs(1-x)Sb(x) NWs by tuning the antimony (Sb) composition. This claim is substantiated by high-resolution transmission electron microscopy combined with photoluminescence spectroscopy. The pure InAs nanowires generally show a mixture of wurtzite (WZ) and zinc-blende (ZB) phases, where addition of a small amount of Sb (∼2-4%) led to quasi-pure WZ InAsSb NWs, while further increase of Sb (∼10%) resulted in quasi-pure ZB InAsSb NWs. This ph… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

8
91
0

Year Published

2015
2015
2024
2024

Publication Types

Select...
9

Relationship

1
8

Authors

Journals

citations
Cited by 60 publications
(99 citation statements)
references
References 65 publications
8
91
0
Order By: Relevance
“…For Aucatalyzed grown nanowires, a transition from WZ/ZB polytypism to pure ZB crystal phase occurs at about x = 0.05, 2 while for indium droplet assisted growth the ZB crystal phase becomes dominant at about x = 0.10. 5 These two facts suggest that we should expect to see this structural evolution mirrored by a similar evolution of the bandgap of InAsSb nanowires for increasing antimony composition. The inset of Figure 4b plots the difference between the expected bandgap (for the ZB crystal phase) as a function of antimony composition.…”
Section: Lettermentioning
confidence: 80%
“…For Aucatalyzed grown nanowires, a transition from WZ/ZB polytypism to pure ZB crystal phase occurs at about x = 0.05, 2 while for indium droplet assisted growth the ZB crystal phase becomes dominant at about x = 0.10. 5 These two facts suggest that we should expect to see this structural evolution mirrored by a similar evolution of the bandgap of InAsSb nanowires for increasing antimony composition. The inset of Figure 4b plots the difference between the expected bandgap (for the ZB crystal phase) as a function of antimony composition.…”
Section: Lettermentioning
confidence: 80%
“…In a previous study, we reported the growth of vertically aligned InAs NWs on graphite with highly uniform diameters through optimized In droplets28. The growth of high quality, nontapered and ultrahigh aspect ratio InAs 1−x Sb x NWs was also demonstrated on graphite29. It was shown that NW nucleation and growth is facilitated by the predeposited In droplets.…”
mentioning
confidence: 94%
“…Hence, an investigation of the influence of growth parameters and the conditions for realizing optimal InAs NWs with controlled geometry is crucial. Furthermore, most III-V semiconductor NWs are plagued by the presence of wurtzite (WZ) and zinc-blende (ZB) crystal phase mixtures (polytypism)282930 which function as traps for carriers,31 reduce carrier mobility32 and conductivity33. Polytypism also results in electron scattering at stacking faults or twin planes3435 which is detrimental to their optical properties and device applications.…”
mentioning
confidence: 99%
“…The injection of Sb shows a strongly influence on NW morphology, i.e., axial and lateral growth rate. In terms of crystal phase transition, a detail study from Zhuang et al [230] shows that from WZ/ZB mixed InAs NWs, addition of Sb led to quasi-pure …”
Section: Science China Materialsmentioning
confidence: 99%